ANALISIS YURIDIS SENGKETA HARTA MILIK PRIBADI YANG DIPUTUSKAN OLEH PENGADILAN MENJADI HARTA BERSAMA (STUDI PUTUSAN PENGADILAN NEGERI MEDAN NOMOR 290/Pdt.G/2013/PN.Mdn - FITRI YANTI TAMBUN (PREMISE LAW JURNAL, 2016)
The Law on Marriage Property regulates the legal consequences on the husband and wife’s property. The arrangement of marriage property can be seen from how they obtain the property. The object of the research was the Verdict of Medan District Court No.290/Pdt.G/2013/PN regarding the settlement of the personal property that has been made joint property. The problem discussed in the analysis of this research was: how to classify the property that was received after the marriage has been dissolved and how about the legal consequences toward the inheritance that was not distributed yet, how the trade between mother and son/daughter is in accordance with positive law in Indonesia, and how the judge’s legal considerations were in the Verdict of Medan District Court No.290/Pdt.G/2013/PN.Mdn. the research used descriptive analytical and judicial normative method. Keywords: Marriage Property, Personal Property, Dissolved Marriage